Metabolic Identification Based on Proposed Mass Fragmentation Pathways of the Anabolic Steroid Bolasterone by Gas Chromatography Tandem Mass Spectrometry - Muresan, Anca？Raluca; Rahaman, Khandoker Asiqur; Rafique, Farzana？Binte; Son, Junghyun; Kang, Min-Jung; Kwon, Oh Seung (John Wiley & Sons Ltd., 2025)
Bolasterone (7α,17α-dimethyl-androsta-4-en-17β-ol-3-one) was registered on the World Anti-Doping Agency's Prohibited list of substances. This study was aimed at evaluating the metabolism of bolasterone through in vitro (liver microsomes) and in vivo (rat urine) experiments to propose mass fragmentation pathways of the metabolites by gas chromatography？quadrupole tandem mass spectrometry (GC-EI-MS/MS). Their plausible chemical structures were suggested based on their fragmentation pathways to overcome the lack of available authentic standards. A total of 12 metabolites (5 mono-hydroxylated M1 to M5 and 7 di-hydroxylated M6 to M12) after trimethylsilylation were observed. Key diagnostic ions included m/z 403 (mono-hydroxylated) and m/z 491 (di-hydroxylated) with m/z 143, indicating an intact D ring (M1 to M5, M7, M9, M10, M11). Hydroxylation at the D ring (M6, M12) was characterized by ions m/z 231 or 219. Hydroxylation at the A (M5, M7) or B (M2/M3, M10) rings corresponded to m/z 281 and hydroxylation at C12 of the C ring (M4, M10) was indicated by m/z 285. Based on the comparison with bolasterone analogues such as testosterone and methyltestosterone and the interpretation of fragmentation pathways, the mono-hydroxylation metabolites M1 (at C11), M2/M3 (at C6), M4 (at C12), M5 (at C2), and di-hydroxylation metabolites M6 (at C11 and C16), M7 (at C2 and C11), M10 (at C6 and C12), and M12 (at C12 and C16) were proposed. The hydroxylation sites of M8, M9, and M11 could not be determined. This data can be useful for identifying hydroxylated metabolites by interpreting mass spectra of anabolic steroids with no standards available.